#notokay: Challenging sexual violence through digital health activism. Issue 2 (15th March 2022) - Subramanian, Roma; Weare, Andrea
ABSTRACT: An analysis of #notokay tweets revealed that tweets constructed a grassroots health activist discourse that made visible the 'invisible' pervasiveness of sexual assault by encouraging women to disclose assault in a digital space of affective solidarity. The campaign captured a multiplicity of embodied assault experiences, dispelled rape myths, and challenged and broadened mainstream conceptualizations of assault. It aimed at transformative change by politicizing the public health issue of sexual violence by highlighting the socioenvironmental determinants of assault – a patriarchal culture that condones and fosters violence against women and does not prioritize women's health. By offering rich qualitative data on the magnitude, characteristics, and consequences of sexual violence via the lived experiences of women shared through tweets, digital health activist campaigns like #notokay have the potential to complement traditional public health surveillance systems of violence against women, and thereby raise the visibility of this issue.